Pelatihan Media Sosial Bilingual untuk Promosi Berkelanjutan: Studi Kasus Karang Taruna Dwikora Medan: Bilingual Social Media Training for Sustainable Promotion: A Community Service Program for Karang Taruna Dwikora Medan - Ananda, Zhafran Fatih; Aurlani, Febry; Pratama, Andre (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Social media has become a strategic medium in modern communication, including for the sustainable promotion of products and services. Recognizing the importance of practical communication skills on digital platforms, this community service activity aimed to provide training for the Karang Taruna Dwikora Medan on socialization of using English and Indonesian for sustainable promotion on social media. The training was conducted over two days using a participatory approach, involving presentations, discussions, and hands-on practice. The materials covered include using social media as a promotional tool, techniques for creating sustainable content, and language strategies such as code-switching, bilingual hashtags, and content adaptation based on the platform. This activity showed a significant increase in participants' understanding and ability to design engaging and relevant promotional content for local and international audiences, with an 85% improvement in knowledge based on pretest and posttest evaluations. The participants' enthusiasm and active participation demonstrated this program's success in raising awareness of the importance of adaptive and inclusive communication strategies in the digital age. This activity made a real contribution to youth empowerment by mastering digital communication skills oriented toward sustainability.